2017
DOI: 10.1038/tp.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression associated with suicide attempts in US veterans

Abstract: According to a recent report from the Office of Suicide Prevention in the US Department of Veterans Affairs, veterans represent 8.5% of the US population, but account for 18% of all deaths from suicide. The aim of this study of psychiatric patients (n=39; 87% male) was to compare blood gene expression data from veterans with a history of one or more suicide attempts to veterans who had never attempted suicide. The attempter and non-attempter groups were matched for age and race/ethnicity, and both groups inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Beyond these risk factors, suicide is a very complicated behavior, which may be affected by the interaction of physical, psychological, and socioeconomic factors at the same time. Thus, more factors should be taken into accounts, such as posttraumatic stress disorder (PTSD) [ 66 ], depression [ 13 , 14 ], cardiovascular disease [ 67 ], opioid prescriptions [ 68 ], education level [ 69 ], or even genetic level [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these risk factors, suicide is a very complicated behavior, which may be affected by the interaction of physical, psychological, and socioeconomic factors at the same time. Thus, more factors should be taken into accounts, such as posttraumatic stress disorder (PTSD) [ 66 ], depression [ 13 , 14 ], cardiovascular disease [ 67 ], opioid prescriptions [ 68 ], education level [ 69 ], or even genetic level [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has discovered depression is significantly correlated with suicide, and the suicide rate in depression patients far exceeds that in ordinary people 6 8 . During the COVID-19 outbreak and resulting quarantine, suicidal intention and action quickly increased in high-risk groups, including unemployed 9 , bereaved 10 , smoking 11 , alcohol consumption 12 – 14 , or even genetic level groups 15 , 16 . Although cancer patients of both genders underwent identical stress, drastic decline of family income possibly intensified the suicidal intention and action among men 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 56 unique miRNAs were identified that differed significantly in their expression between suicide victims and control subjects. These miRNAs identified are included in various pathways, including some previously associated with suicidal behavior, including neurogenesis [45], inflammation and stress responses [46]; Wnt signaling [47]; and the polyamine system [48]. However, no single clear direction arises from these pathways identified, which indicates the complexity and divergence of the miRNA networks.…”
Section: Discussionmentioning
confidence: 99%